Red Meat Intake and Risk of Leukemia: A Protocol of Systematic Review and Meta-Analysis - Soleimani, Yaser; Sadeghi, Parniyan; Talebi Taheri, Abdolkarim; Asadipour, Fatameh; Azizi, Fatemeh; Khavari, Tina; Karimiyan, Mobina; Halimi, Aram; Mosavi Jarrahi, Alireza (Asian Pacific Journal of Cancer Biology, 2023)
Background: The intricate interplay of risk factors and their modifying effects on health outcomes, known as effect modification, remains a critical and complex phenomenon in epidemiological research. In this study, we rigorously explore the dimensions of effect modification, focusing on its quantification, qualitative and quantitative manifestations, and implications for both research and practice. Drawing on a comprehensive analysis of existing literature, we examine the challenges and opportunities in identifying and understanding these interactions among variables. Methods: This investigation adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines, employing a meticulous search strategy to identify relevant studies from electronic databases. Studies exploring the association between red meat intake and the risk of leukemia are meticulously selected, with data extraction encompassing study characteristics, exposure assessment methods, outcome evaluation, and adjusted effect estimates. Results: The synthesis of the selected studies is conducted using random-effects meta-analysis to estimate the pooled effect size of red meat intake on leukemia risk. Subgroup analyses dissect potential sources of heterogeneity, accounting for variations in study design, population characteristics, and geographic location. Sensitivity analyses assess the robustness of the results, scrutinizing the influence of individual studies on the overall effect estimate. A dose-response analysis examines potential trends in the relationship between different levels of red meat consumption and leukemia risk. Conclusion: Through a systematic review and meta-analysis augmented by the GRADE assessment, this study aims to contribute rigorous evidence on the relationship between red meat intake and leukemia risk. By quantifying the effect size, exploring sources of heterogeneity, and integrating GRADE, we endeavor to offer a comprehensive evaluation that informs future research directions and underscores the potential impact on public health recommendations.